REASONS BEHIND DISTINCTION IN LIFE EXPECTANCY OF DEVELOPED COUNTRIES AND DEVELOPING COUNTRIES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
In the medieval ages, people usually had concise life spans but life expectancy grew as the standard of life and medicine grew. Today life expectancy is different in all countries, however, people in developed countries are known to live longer than those in developing countries. In this article we will learn about the main factors leading to longer life spans in developed countries and the causes of shorter life expectancy in developing countries and make a general conclusion.